The genealogical construction of the Kyrgyz Republic kinship, state and "tribalism" - Gullette, David (Inner Asia series ;, 2010)
In this important new study on the peoples of the Kyrgyz Republic (Kyrgyzstan), David Gullette exposes significant misconceptions that have hitherto shaped Western understanding about the role of kinship in Kyrgyz society and offers new insights into notions of relatedness.